If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -6y = 0 Solving 1 + -6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -6y = 0 + -1 -6y = 0 + -1 Combine like terms: 0 + -1 = -1 -6y = -1 Divide each side by '-6'. y = 0.1666666667 Simplifying y = 0.1666666667
| (3x+1)(2x-8)-6x(x+4)= | | -16x^2+156x+60= | | 16x^2-156x-60= | | 4x-7+2(4x+5)=-2(x+2) | | 5x^2-20x-11= | | 2(v-9)-2=-4(-5v+4)-2v | | 5x^2-20x-3= | | 5x^2+6x-44= | | 2-(y-5)(7-2y)-y(2y-3)= | | -2(8w-1)+4w=6(w+2) | | 4u+3-5(-2u-1)=6(u-1) | | 2x-5*2=10 | | 2y+(5-7y)-9-(3y-2)= | | f(x)=x^3-2.25x^2-3x | | x+2*4=4 | | 427xX=X | | x+0y=4 | | Y+3z=10 | | x-6=-31 | | x(x+3)(x+3)=x(x-3)(x+3) | | 6-4(x+5)=-16 | | K=9r-a | | 2x^2+y^2=17 | | -4(y+5)=8-6(y+7) | | 7y-(8y+9)=10 | | 2x^4+20x^2+18=0 | | 5x=3x-4x+10+2 | | -4(-2)(-5)= | | 4+5=445 | | [(x^3+4X)(6X+2)]+[(3X^2+2X-5)(3X^2+4)]= | | 4+4=445 | | X=(x+500)+4x-1100 |